Community science informs movement and reproductive ecology of sand tigers Carcharias taurus off North Carolina, United States of America - Price, Carol Seals; McClanahan, Ara Lupton; Burge, Erin J.; Houppermans, Tanya; Holmberg, Jason (Frontiers in Marine Science, 2024)
Sand tigers are frequently observed at shipwrecks and other artificial reef habitats off North Carolina (USA), but data about occupancy, movement ecology, and site fidelity are lacking. Spot A Shark USA researchers used Wildbook© photoidentification software to spot map sand tigers in images provided by recreational SCUBA divers, or collected from remotely operated vehicles, and an offshore live-streaming camera. We uniquely identified 1837 sand tigers, 101 of which were resighted on more than one date between 2005-2021. Sand tigers of both sexes and various ages were found year-round along the northern, central and southern coast. We identified shipwrecks or artificial reef sites with consistently high numbers of shark encounters reported, sometimes with seasonal occupancy patterns. Resighted sharks were often encountered at the same or nearby locations, confirming high levels of residency and site fidelity to specific locations. Together, the mating scars seen on 121 female sand tigers and 202 females documented with rotund abdomens consistent with pregnancy highlight the importance of NC waters for reproduction. We also quantified other characteristics of the sand tigers visible in the photographs including wounds, parasitic copepods, and attached fishing gear. Our results reflect the importance of habitats off the NC coast to the movement and reproductive ecology of sand tigers at multiple life history stages. Sand tiger populations have declined in the Northwest Atlantic, so information about residence at specific locations, seasonal patterns of occupancy, and sex-dependent behaviors associated with migration and reproduction are important to future management and conservation of the species.